Analysis of the existence of a culture of organizational listening, from managers in the multi-store sector in Chile - Claro, Cecilia (2021)
Communication in organizations is becoming more complex every day since the reality of companies acquires a physiognomy, which demands greater responsibility from them, at the same time as a more efficient and committed management with the public with whom it interacts and a relationship with them it has a more permanent character. It is in this understanding that organizational listening becomes a necessary intangible to work on them, since it is necessary to understand in a better and more direct way what are the requirements of the public with whom they interact and generate links, what is it constitutes an important dimension of company management. The purpose of this study is to know the perceptions about whether organizational listening processes are being carried out in the retail sector in Chile and whether a culture that encourages its execution has been adopted. For this purpose, executives working in the areas of marketing, communications and people management are interviewed, questionnaires are carried out and official documents are analyzed in order to know the state of the matter in order to know the state of the matter and if effective listening has positive consequences for organizations.